2023
DOI: 10.31234/osf.io/s8mwv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of 97 studies reveals that statistical learning and language ability are only weakly correlated

Sam Boeve,
Haoyu Zhou,
Louisa Bogaerts

Abstract: Despite the widely held belief that individual differences in statistical learning (SL) abilities are associated with linguistic skills, research has produced mixed results. To provide a comprehensive assessment of the literature, we conducted a meta-analysis of 97 studies examining the correlation between SL and linguistic abilities. Results revealed a small but significant overall correlation (r = .16). Our analysis considered sample characteristics, SL task features, and the type of language test as predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Subsequent investigations have demonstrated that learners of all ages (Campbell et al, 2012;Fló et al, 2019Fló et al, , 2022Saffran et al, 1997;Teinonen et al, 2009) can use the regularities naturally present in their environment to track statistical patterns across sensory domains highlighting the broad importance of this learning mechanism (Conway & Christiansen, 2005;Fiser & Aslin, 2002;Kirkham et al, 2002;Saffran et al, 1999). Although there are both individual differences (Siegelman & Frost, 2015) and developmental change in statistical learning (Forest, Abolghasem, et al, 2023;Jung et al, 2020;Raviv & Arnon, 2018), this process is well-known to support much of the environmental learning which pervades early life, and predicts later behaviors such as reading ability (Arciuli & Simpson, 2012;Spencer et al, 2015), and linguistic performance (Boeve et al, 2023;Kidd & Arciuli, 2016;Misyak & Christiansen, 2012;Shafto et al, 2012;Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent investigations have demonstrated that learners of all ages (Campbell et al, 2012;Fló et al, 2019Fló et al, , 2022Saffran et al, 1997;Teinonen et al, 2009) can use the regularities naturally present in their environment to track statistical patterns across sensory domains highlighting the broad importance of this learning mechanism (Conway & Christiansen, 2005;Fiser & Aslin, 2002;Kirkham et al, 2002;Saffran et al, 1999). Although there are both individual differences (Siegelman & Frost, 2015) and developmental change in statistical learning (Forest, Abolghasem, et al, 2023;Jung et al, 2020;Raviv & Arnon, 2018), this process is well-known to support much of the environmental learning which pervades early life, and predicts later behaviors such as reading ability (Arciuli & Simpson, 2012;Spencer et al, 2015), and linguistic performance (Boeve et al, 2023;Kidd & Arciuli, 2016;Misyak & Christiansen, 2012;Shafto et al, 2012;Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%